2018
DOI: 10.1177/0046958018779654
|View full text |Cite
|
Sign up to set email alerts
|

How Do the Hospital Prices Paid by Medicare Advantage Plans and Commercial Plans Compare With Medicare Fee-for-Service Prices?

Abstract: The prices that private insurers pay hospitals have received considerable attention in recent years, but most of that literature has focused on the commercially insured population. Although nearly one-third of Medicare beneficiaries are enrolled in a Medicare Advantage (MA) plan, little is known about the prices paid to hospitals by the private insurers that administer such plans. More information on the hospital prices paid by MA plans would provide additional insights into whether MA prices are more closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…These findings are surprising because prior research has found that private insurers typically pay more than Medicaid, 8,16 and Medicare rates. 3,6,[8][9][10] Although median prices paid by private insurers in Maine and Connecticut were similar to Medicaid rates for fluoride varnish in these states, these states' Medicaid agencies pay for fluoride varnish plus additional preventive oral health services (i.e., risk assessment and/or oral evaluation), just like 14 other Medicaid agencies. 37 The combined Medicaid payments for "fluoride varnish plus" were substantially higher than prices paid by private insurers for nearly fluoride varnish claims-more than double the median price paid by private insurers for fluoride varnish in these states.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These findings are surprising because prior research has found that private insurers typically pay more than Medicaid, 8,16 and Medicare rates. 3,6,[8][9][10] Although median prices paid by private insurers in Maine and Connecticut were similar to Medicaid rates for fluoride varnish in these states, these states' Medicaid agencies pay for fluoride varnish plus additional preventive oral health services (i.e., risk assessment and/or oral evaluation), just like 14 other Medicaid agencies. 37 The combined Medicaid payments for "fluoride varnish plus" were substantially higher than prices paid by private insurers for nearly fluoride varnish claims-more than double the median price paid by private insurers for fluoride varnish in these states.…”
Section: Discussionmentioning
confidence: 88%
“…[1][2][3][4][5][6] Studies find higher prices among private insurers than Medicare and Medicaid. 3,[6][7][8][9][10] These studies, however, are generally focused on adults, hospital prices, and comparisons between private insurers and Medicare, which rarely covers pediatric services. 11 Research has typically focused on comparisons to Medicare which is a national program with prices set administratively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicare Fee-for-Service [FFS], Medicaid Advantage [MA], and Medicaid versus commercial) but were anchored to the FFS reimbursement rates captured through the 2019 Medicare Fee Schedules and adjusted to 2020 US dollars using the medical care component of the US Consumer Price Index. The reimbursement for commercial plans was inflated by 89% over FFS rates 32 , while other plan types were set equal to FFS rates. FFS reimbursement rates reflect the mean base Diagnosis-Related Group (DRG) and add-on payments to hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…HCRU and costs are usually different for those enrolled in commercial health insurance compared with those enrolled in MAPD plans (majority are aged 65 years and older). [22][23][24] Additionally, because the study population was predominantly enrolled in MAPD plans (~90%), the HCRU and costs were reported only for those enrolled in MAPD plans during the measurement year and follow-up year.…”
Section: Patient Selectionmentioning
confidence: 99%